Design of the new couplers for C-ADS RFQ - 石爱民 孙列鹏 张周礼 徐显波 施龙波 李晨星 王文斌 (Chinese physics C, 2015)
A new special coupler with a kind of bowl-shaped ceramic window for a proton linear accelerator named the Chinese Accelerator Driven System （C-ADS） at the Institute of Modern Physics （IMP） has been simulated and constructed and a continuous wave （CW） beam commissioning through a four-meter long radio frequency quadruple （RFQ） was completed by the end of July 2014. In the experiments of conditioning and beam, some problems were promoted gradually such as sparking and thermal issues. Finally, two new couplers were passed with almost 110 kW CW power and 120 kW pulsed mode, respectively. The 10 mA intensity beam experiments have now been completed, and the couplers during the operation had no thermal or electro-magnetic problems. The detailed design and results are presented in the paper.